Hardiness Counseling to Enhance Student Academic Resilience - Sanjaya, Eka; Yustiana, Yusi Riksa (Academia Edu Cendekia Indonesia (AEDUCIA), 2023)
Currently, students are expected to excel and make significant contributions in various sectors such as education, technology, the economy, and social aspects as the year 2045 approaches. Resilience in facing challenges (hardiness) has the potential to support academic resilience. The aim of this research is to test the effectiveness of Hardiness Counseling in enhancing academic resilience. This article has undergone a review and analysis process to illustrate how training in developing hardiness can have a positive impact on resilience against stress in Indonesian adolescents, in line with the vision of Indonesia Emas 2045. The results of the literature analysis underscore the importance of hardiness training as a relevant step toward achieving the goals of Indonesia Emas 2045.